Method for preparing hard carbon material from carbon precursor and application of hard carbon material

By preparing waste materials such as activated carbon, biomass carbon, coke, etc. into hard carbon materials, the rich pore structure is used to solve the performance and life of sodium ion batteries, and the low-cost negative electrode materials suitable for large-scale production are realized, which improves the battery's Energy density and cycling performance.

CN119284881APending Publication Date: 2025-01-10GUILIN UNIV OF ELECTRONIC TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411720602.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

It is difficult to find cheap and suitable for mass production of sodium ion batteries in the prior art, and the performance and life of sodium ion batteries are affected by structural changes in the process of sodium ion embedding and detachment of graphite materials.

Method used

Use waste materials such as activated carbon, biomass carbon, and coke as precursors to prepare hard carbon materials through pretreatment and two-stage high-temperature hard carbonization process, and use its rich pore structure to improve energy storage capacity and circulation performance.

Benefits of technology

It effectively improves the specific capacity and battery energy density of hard carbon negative electrode materials, realizes resource recycling, is suitable for industrial production, and significantly improves the circulation and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284881A_ABST
    Figure CN119284881A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a hard carbon material from a carbon precursor and application of the hard carbon material, activated carbon, biomass charcoal, coke and polymer derived carbon are used as raw materials, and the hard carbon material is prepared through the procedures of pretreatment, high-temperature hard carbonization, crushing and the like. The preparation method is simple in process, wide in raw material source, low in cost and suitable for large-scale industrial production. The hard carbon material prepared by the invention is used as an alkali metal ion battery negative electrode material, and shows high specific capacity, excellent rate capability and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for alkali metal ion batteries, and specifically relates to a method for preparing a hard carbon material from a carbon precursor and application thereof. Background Art

[0002] In today's production and life, energy storage brings us a lot of convenience, such as electric bicycles, mobile phones, computers, etc. Due to the shortage of fossil fuel resources and their damage and pollution to the environment, new renewable energy has become our next research direction. Solar energy, wind energy, hydropower, etc. have a lot of room for utilization. Then, a large amount of energy needs to be stored after collection. Correspondingly, the battery industry has to develop rapidly. Lithium-ion batteries have become the first choice in the field of energy storage due to their high energy density and working voltage. While lithium-ion batteries are developing, they are also facing problems such as shortage of lithium resources and high costs. Their substitutes such as sodium-ion batteries and potassium-ion batteries have received widespread attention. Compared with other metal-ion batteries, sodium-ion batteries, as a hot research field of alkali metal batteries, have the advantages of high safety, wide range of raw materials, and excellent high and low temperature performance. New energy storage, low-speed electric vehicles, 5G communication base stations and other fields all need the strong advantages of sodium-ion batteries. Sodium-ion batteries can use the mature technology and many equipment of lithium-ion batteries. Graphite material as the negative electrode of lithium-ion battery shows good lithium storage capacity, but due to the large radius of sodium ions, the extraction and embedding process in graphite will cause large structural changes, reducing the performance and life of sodium-ion batteries. The negative electrode of sodium-ion batteries still requires us to find a suitable negative electrode material. Biomass hard carbon is a very popular negative electrode material at present, with a wide source, high carbon content, and low price, which is in line with the concept of green development.

[0003] A large number of studies have shown that hard carbon has a larger interlayer spacing and a large number of microporous structures, which can provide more sodium storage sites and effectively promote the embedding and extraction of alkali metal ions. Hard carbon negative electrodes can be widely used in lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, supercapacitors and other fields. However, the current high-performance hard carbon is mostly made of biomass and polymers. Due to the problems of low carbon yield, complex process and high cost, the research and development of negative electrode materials has encountered a large bottleneck. At present, it is difficult to find cheap precursor materials suitable for large-scale mass production.

[0004] Carbon materials have three allotropes according to the different arrangements of their atoms in the structure, namely diamond, graphite and amorphous carbon, and their physical properties, chemical properties and uses are also different. Amorphous carbon has a rich porous structure. In addition, materials with disordered or disordered structures have more stable chemical properties, and their open structures are more conducive to the embedding of ions, making them suitable for electrochemical energy storage materials. Common amorphous carbons include activated carbon, coke, wood charcoal, etc. Activated carbon is prepared by pyrolysis and activation of carbon-containing raw materials such as wood, coal and petroleum coke. It has a developed pore structure, a large specific surface area and rich surface chemical groups, and is a general term for carbon materials with strong specific adsorption capacity. Activated carbon is widely used in life, such as sewage treatment, air purification and environmental protection. At the same time, activated carbon is suitable as an electrode material for batteries and supercapacitors due to its rich pore structure. Biomass charcoal has a wide range of sources, mainly including forest residues, agricultural residues (such as corn stalks, straw, etc.), urban solid waste, energy crops, and animal manure. These biomasses can be prepared into biochar through thermochemical conversion processes such as high-temperature pyrolysis in an oxygen-deficient environment. Biochar, coke and other materials have considerable capacity when used as battery negative electrode materials.

[0005] The carbon material used in the present invention mainly comes from waste activated carbon materials, biomass, coke, etc. These materials have low utilization rates in life and will pollute the environment, making them difficult to use. Using carbon materials as precursors for hard carbon negative electrode materials for batteries, on the one hand, these waste and low-cost materials can be utilized, which increases the value while also protecting the environment; on the other hand, carbon materials have rich porous structures, provide active sites suitable for the storage of alkali metal ions, and have considerable capacity. The hard carbon material used in this experiment has a simple manufacturing process and a large amount of material processed at one time, which is suitable for industrial production.

[0006] In summary, the present invention provides a method for preparing hard carbon materials from carbon precursors, which effectively utilizes the developed microporous structure of hard carbon materials and improves the energy storage capacity of negative electrode materials through a simple treatment process. The preparation method of the present invention has a simple process, a wide source of raw materials, low cost, and can be mass-produced industrially. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a hard carbon material and to use it as a negative electrode material for an alkali metal ion battery. This invention uses activated carbon, biochar, coke, and polymer-derived carbon as precursor raw materials, and prepares the hard carbon material through pretreatment, two-stage high-temperature hard carbonization, and crushing. In this process, the original rich pore structure of the precursor is fully utilized, which effectively improves the specific capacity of the hard carbon material. At the same time, the carbon material has a stable skeleton structure and a low working potential, which improves the cycle and rate performance of the battery.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing a hard carbon material from a carbon precursor comprises the following steps:

[0010] The first step is precursor pretreatment: the precursor is roughly crushed into particles, fully impregnated with a certain proportion of acid or alkali solution, then ultrasonically cleaned and filtered with deionized water, and dried to a water content of 5wt% to 20wt% to obtain an intermediate product.

[0011] In the second step, the intermediate product is placed in a high-temperature tubular furnace, and heated to 800-1100°C and 1200-2000°C in two stages at a heating rate of 6-15°C / min and 1-5°C / min, and the sintering time is 0.5-4h and 1-6h. After natural cooling, it is ground and passed through a 300-1000 mesh sieve to obtain the required hard carbon material.

[0012] Preferably, in the first step, the precursor is selected from activated carbon, biochar, coke, and polymer-derived carbon.

[0013] Preferably, in the first step, the concentration of the acid or alkali solution in the immersion process is 9% to 90%.

[0014] Preferably, in the first step, the acid solution for acid immersion is a mixed solution of hydrofluoric acid and at least one of hydrochloric acid, phosphoric acid, sulfuric acid and hydrochloric acid.

[0015] Preferably, in the first step, the alkali solution for alkali solution impregnation includes at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.

[0016] Preferably, in the first step, the mass ratio of the acid solution or alkali solution to the precursor is 0.5-30.

[0017] Preferably, in the first step, the precursor is immersed in an acid solution or an alkali solution for 1 hour to 24 hours.

[0018] Preferably, in the first step, the acid solution or alkali solution immersion treatment temperature is 20-80°C.

[0019] Preferably, in the first step, the raw material needs to be repeatedly rinsed with deionized water until the solution is neutral.

[0020] Preferably, in the first step, the water content of the intermediate product is 5wt% to 10wt%.

[0021] Preferably, in the second step, the protective atmosphere is at least one of nitrogen, argon, vacuum and ammonia, and the protective gas rate is 1 to 1000 ml / min.

[0022] Preferably, in the second step, the first stage heating rate is 6-10°C / min, the sintering temperature is 1000-1100°C, and the sintering time is 2-3h.

[0023] Preferably, in the second step, the second stage heating rate is 2-5°C / min, the sintering temperature is 1300-1600°C, and the sintering time is 2-4h.

[0024] Preferably, in the second step, the mesh size of the sieve is 300 to 500 meshes.

[0025] The second object of the present invention is to provide a hard carbon material, wherein the specific surface area of ​​the material is ≤27m 2 / g, tap density ≥0.50g / cm 3 , average particle size D50≤20μm.

[0026] The invention also provides an application of the hard carbon material as a negative electrode material of an alkali metal ion battery.

[0027] The third object of the present invention is to provide an alkali metal ion battery, which is composed of a positive electrode, a separator, an electrolyte and a hard carbon negative electrode.

[0028] Preferably, in the present invention, the negative electrode of the battery comprises a hard carbon material, a binder, a conductive agent, etc., wherein the binder is at least one material selected from the group consisting of PVDF, CMC, SBR, PTFE, SA, PAA, PAN, etc.

[0029] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0030] The hard carbon material prepared by the present invention uses waste activated carbon, biochar, coke, and polymer-derived carbon as precursors, giving full play to the advantages of cheap precursor raw materials and wide sources, and utilizing the rich micro-nanopores in the internal structure of the precursor material to provide sufficient energy storage sites, thereby improving the specific capacity of the hard carbon negative electrode and the energy density of the battery. The preparation method is simple and has the characteristics of large-scale production. At the same time, the present invention effectively utilizes waste carbon materials and realizes resource recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the nitrogen adsorption-desorption curve of the negative electrode material provided in Example 1 of the present invention.

[0032] Figure 2 This is a charge and discharge curve diagram of the negative electrode material provided in Example 2 of the present invention.

[0033] Figure 3 This is a cycle performance diagram of the negative electrode material provided in Example 2 of the present invention.

[0034] Figure 4 This is a charge and discharge curve diagram of the negative electrode material provided in Example 4 of the present invention.

[0035] Figure 5 This is a cycle performance diagram of the negative electrode material provided in Example 5 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] Example 1

[0038] This example provides a method for preparing hard carbon materials using activated carbon precursors and its application.

[0039] The preparation steps of hard carbon materials are as follows:

[0040] (1) Pretreatment of the precursor: The activated carbon precursor material prepared in advance is placed in a container, and the precursor is treated by impregnation with a mixed solution of hydrochloric acid and hydrofluoric acid with a concentration of 1 mol / L. After deionization and cleaning, it is impregnated with a 1 mol / L potassium hydroxide solution, wherein the amount of the mixed acid solution and potassium hydroxide solution added is equal to the mass of the precursor raw material. After ultrasonic treatment for 15 minutes, it is impregnated for 24 hours, rinsed with deionized water, filtered, and dried until the moisture content of the material is about 10wt%.

[0041] (2) Two-stage high-temperature carbonization: 1 kg of pretreated precursor material was placed in a tubular furnace with inert nitrogen gas flowing through it at a flow rate of 200 mL / min. The temperature was raised to 800 °C at a heating rate of 10 °C / min and kept at that temperature for 2 h. The temperature was then raised to 1200 °C at a rate of 5 °C / min for high-temperature hard carbonization treatment and kept at that temperature for 2 h. The gas in the furnace was maintained at about 0.02 MPa.

[0042] (3) Cooling: After the hard carbonization is completed, maintain the protective atmosphere until it cools naturally to room temperature.

[0043] (4) Crushing and grading: crushing and grading the obtained materials.

[0044] This example also provides a hard carbon material, which is prepared by the above method, and has a particle size distribution of 3-40 μm and a D50 particle size of 17 μm.

[0045] The nitrogen adsorption-desorption curve of the hard carbon material provided in this embodiment is as follows: Figure 1 As shown, it can be seen that the specific surface area of ​​the hard carbon material is 27m 2 / g, and its relatively large specific surface area is due to the well-developed pore structure of the precursor activated carbon.

[0046] This example also provides the application of hard carbon materials as negative electrode materials for sodium ion batteries. At a current density of 30 mA / g, the first coulombic efficiency of the negative electrode material is 83.6% (see Table 1), the reversible specific capacity is 209.3 mAh / g, and after 50 cycles, the capacity retention rate is 93.6%.

[0047] Example 2

[0048] This example provides a method for preparing hard carbon materials from biomass carbon precursors and its application.

[0049] The preparation method of the hard carbon material is substantially the same as that of Example 1. The difference is that:

[0050] (1) The precursor is biochar, and the concentration of the sodium hydroxide solution and the mixed solution of sulfuric acid and hydrofluoric acid used in the precursor pretreatment is 1.5 mol / L. The amount of sodium hydroxide solution and the mixed acid solution added is 1.5 times the mass of the precursor raw material. After ultrasonic treatment for 18 minutes, the mixture is immersed for 20 hours and dried until the moisture content of the material is 8wt%;

[0051] (2) 1.5 kg of the pretreated precursor material was placed in a tubular furnace. Inert nitrogen gas was passed through the furnace. The flow rate of nitrogen was controlled at 200 mL / min. The temperature was raised to 900 °C for carbonization at a heating rate of 7 °C / min and kept at that temperature for 3 h. The temperature was then raised to 1400 °C at a heating rate of 5 °C / min for high-temperature hard carbonization treatment. The temperature was kept at that temperature for 2.5 h. The gas in the furnace was maintained at about 0.02 MPa.

[0052] This embodiment also provides a hard carbon material, which is prepared by the above method. When the hard carbon material is used as a negative electrode material for a battery, the first coulombic efficiency is as high as 91.7%, and the first reversible specific capacity is as high as 272.5 mAh / g ( Figure 2 ), after 30 cycles, the capacity retention rate is 96.4% ( Figure 3 ).

[0053] Example 3

[0054] This example provides a method for preparing hard carbon materials from a coke precursor and its application.

[0055] The preparation method of the hard carbon material is substantially the same as that of Example 1, except that:

[0056] (1) The precursor is coke, the concentration of the mixed solution of phosphoric acid and hydrofluoric acid used in the precursor pretreatment is 3 mol / L, the amount of sodium hydroxide solution and mixed acid solution added is twice the mass of the precursor raw material, after ultrasonic treatment for 20 minutes, immersion for 22 hours, and drying until the moisture content of the material is 5wt%;

[0057] (2) 2 kg of pretreated precursor material was placed in a tubular furnace. Inert nitrogen gas was passed through the furnace. The flow rate of nitrogen was controlled at 200 mL / min. The temperature was raised to 800 °C for carbonization at a rate of 8 °C / min and kept at that temperature for 0.5 h. The temperature was then raised to 1200 °C at a rate of 2 °C / min for high-temperature hard carbonization treatment. The temperature was kept at that temperature for 3 h. The gas in the furnace was maintained at about 0.02 MPa.

[0058] This embodiment also provides a hard carbon material, which is prepared by the above method, and has a particle size distribution of 5-45 μm and a D50 particle size of 12.8 μm. The hard carbon material is used as a negative electrode material for a battery, and the first reversible specific capacity is 161.8 mAh / g and the first coulombic efficiency is 82.6%.

[0059] Example 4

[0060] This example provides a method for preparing hard carbon materials using a polymer-derived carbon precursor and its application.

[0061] The preparation method of the hard carbon material is substantially the same as that of Example 1, except that:

[0062] (1) The precursor is polymer-derived carbon. The concentration of the sodium hydroxide solution used in the precursor pretreatment is 1.5 mol / L, the concentration of the mixed solution of sulfuric acid and hydrofluoric acid is 1 mol / L, and the amount of the sodium hydroxide solution and the mixed acid solution added is 2.5 times the mass of the precursor raw material. After ultrasonic treatment for 22 minutes, the mixture is immersed for 18 hours and dried until the moisture content of the material is 12 wt%;

[0063] (2) 2.5 kg of the pretreated precursor material was placed in a tubular furnace. Inert nitrogen gas was passed through the furnace. The flow rate of nitrogen was controlled at 200 mL / min. The temperature was raised to 1000 °C for carbonization at a rate of 10 °C / min and kept at that temperature for 3 h. The temperature was then raised to 1300 °C for high-temperature hard carbonization at a rate of 2 °C / min and kept at that temperature for 6 h. The gas in the furnace was maintained at about 0.02 MPa.

[0064] This embodiment also provides a hard carbon material, which is prepared by the above method. When the hard carbon material is used as a negative electrode material for a battery, the first coulomb efficiency is 89.1%, and the reversible capacity is as high as 308.6 mAh / g ( Figure 4 ).

[0065] Example 5

[0066] This example provides a method for preparing hard carbon materials from biomass carbon precursors and its application.

[0067] The preparation method of the hard carbon material is substantially the same as that of Example 1, except that:

[0068] (1) The precursor is biochar, and the concentration of the sodium hydroxide solution and the mixed solution of hydrochloric acid and hydrofluoric acid used in the precursor pretreatment is 2 mol / L. The amount of sodium hydroxide solution and the mixed acid solution added is 1.5 times the mass of the precursor raw material. After ultrasonic treatment for 22 minutes, the mixture is immersed for 18 hours and dried until the moisture content of the material is 10wt%;

[0069] (2) 3 kg of pretreated precursor material was placed in a tubular furnace. Inert nitrogen gas was passed through the furnace. The flow rate of nitrogen was controlled at 200 mL / min. The temperature was raised to 1100 °C for carbonization at a rate of 15 °C / min and kept at that temperature for 4 h. The temperature was then raised to 1650 °C at a rate of 2 °C / min for high-temperature hard carbonization treatment. The temperature was kept at that temperature for 2 h. The gas in the furnace was maintained at about 0.02 MPa.

[0070] This embodiment also provides a hard carbon material, which is prepared by the above method. The tap density of the hard carbon material is 0.52 g / cm 3 The hard carbon material was used as the negative electrode material of the battery, and the initial coulombic efficiency reached 91.6%, the initial reversible specific capacity was 281.2 mAh / g, and after 20 cycles, the capacity remained at 288.2 mAh / g ( Figure 5 ).

[0071] Comparative Example 1

[0072] This comparative example provides a hard carbon material of an activated carbon precursor, and its preparation method is basically the same as that of Example 1, except that the pretreated activated carbon precursor is crushed and sieved through 300 meshes, and then subjected to high temperature hard carbonization treatment at 1200°C under nitrogen for 2 hours to obtain a hard carbon material. When used as a negative electrode material for a battery, at a current density of 30 mA / g, the first specific capacity is 194.5 mAh / g, and the first coulombic efficiency is 83.2%.

[0073] Comparative Example 2

[0074] This comparative example provides a hard carbon material of a biomass carbon precursor, and its preparation method is basically the same as that of Example 2, except that the bamboo is not treated with acid or alkali impregnation.

[0075] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first specific capacity is 265.4 mAh / g and the first coulombic efficiency is 92.5%.

[0076] Comparative Example 3

[0077] This comparative example provides a hard carbon material of a coke precursor, and its preparation method is basically the same as that of Example 3, except that: the coke precursor material is not subjected to alkali-acid impregnation treatment.

[0078] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first reversible specific capacity is 149.2 mAh / g and the first coulombic efficiency is 80.9%.

[0079] Comparative Example 4

[0080] This comparative example provides a hard carbon material derived from a phenolic resin precursor, and its preparation method is basically the same as that of Example 4, except that the phenolic resin is not subjected to alkali-acid impregnation treatment.

[0081] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first reversible capacity is 291.7 mAh / g and the first coulombic efficiency is 87.9%.

[0082] Comparative Example 5

[0083] This comparative example provides a hard carbon material of a eucalyptus-derived precursor, and its preparation method is basically the same as that of Example 5, except that the eucalyptus is not subjected to acid-base impregnation treatment.

[0084] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first specific capacity is 258.9 mAh / g and the first coulombic efficiency is 89.6%.

[0085] Comparative Example 6

[0086] This comparative example provides a hard carbon material of a polymer-derived carbon precursor, and its preparation method is basically the same as that of Example 4, except that: (2) 2.5 kg of the pretreated precursor material is placed in a tubular furnace, and the furnace is passed with inert gas nitrogen. The flow rate of nitrogen is controlled at 200 mL / min, and the temperature is increased to 1000°C for carbonization at a rate of 5°C / min, and kept at this temperature for 3 hours. Then, the temperature is increased to 1300°C at a rate of 2°C / min for high-temperature hard carbonization treatment, and kept at this temperature for 6 hours. The gas in the furnace is maintained at about 0.02 MPa.

[0087] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first specific capacity is 301.8 mAh / g and the first coulombic efficiency is 89%.

[0088] Comparative Example 7

[0089] This comparative example provides a hard carbon material of a polymer-derived carbon precursor, and its preparation method is basically the same as that of Example 4, except that: (2) 2.5 kg of the pretreated precursor material is placed in a tubular furnace, and the furnace is filled with inert gas nitrogen. The flow rate of nitrogen is controlled at 200 mL / min, and the temperature is increased to 1000°C for carbonization at a rate of 10°C / min, and kept at this temperature for 3 hours. The temperature is then increased to 1300°C at a rate of 6°C / min for high-temperature hard carbonization treatment, and kept at this temperature for 6 hours. The gas in the furnace is maintained at about 0.02 MPa.

[0090] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first specific capacity is 305.7 mAh / g and the first coulombic efficiency is 88.6%.

[0091] Comparative Example 8

[0092] This comparative example provides a hard carbon material of a polymer-derived carbon precursor, and its preparation method is basically the same as that of Example 4, except that: (2) 2.5 kg of the pretreated precursor material is placed in a tubular furnace, and the furnace is passed with inert gas nitrogen. The flow rate of nitrogen is controlled at 200 mL / min, and the temperature is increased to 1000°C for carbonization at a heating rate of 12°C / min, and kept at this temperature for 3 hours. Then, the temperature is increased to 1300°C at a heating rate of 2°C / min for high-temperature hard carbonization treatment, and kept at this temperature for 6 hours. The gas in the furnace is maintained at about 0.02 MPa.

[0093] The prepared hard carbon material is used as a negative electrode material for a battery. At a current density of 30 mA / g, the first specific capacity is 306.8 mAh / g and the first coulombic efficiency is 88.2%.

[0094] Table 1 Electrochemical properties of hard carbon materials provided by the embodiments of the present invention and comparative examples

[0095] Examples Reversible specific capacity (mAh / g) First coulombic efficiency (%) Example 1 209.3 83.6 Example 2 272.5 91.7 Example 3 161.8 82.6 Example 4 308.6 89.1 Example 5 281.2 91.6 Comparative Example 1 194.5 83.2 Comparative Example 2 265.4 92.5 Comparative Example 3 149.2 80.9 Comparative Example 4 291.7 87.9 Comparative Example 5 258.9 89.6 Comparative Example 6 301.8 89 Comparative Example 7 305.7 88.6 Comparative Example 8 306.8 88.2

[0096] The above description is a detailed description of the preferred embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications completed under the technical concept suggested by the present invention should fall within the scope of the patent covered by the present invention.

Claims

1. A method for preparing a hard carbon material from a carbon precursor, characterized in that: The following steps are involved: S1. Pretreating the carbon precursor, impregnating it with alkali solution and acid solution, ultrasonically cleaning it with deionized water to remove impurities, and drying it to obtain an intermediate product; S2. The intermediate product obtained in S1 is subjected to two-stage high-temperature hard carbonization sintering under a protective atmosphere, naturally cooled, and crushed to obtain a hard carbon material.

2. The method for preparing hard carbon material from a carbon precursor according to claim 1, characterized in that: The carbon precursor is at least one of activated carbon, biomass carbon, coke, and polymer-derived carbon.

3. The method for preparing hard carbon material from a carbon precursor according to claim 1, characterized in that: The alkaline solution and acid solution impregnation described in step S1 can be interchanged with each other; the deionized water ultrasonic cleaning is performed in a neutral solution, and the ultrasonic cleaning includes a filtering and washing process.

4. The method for preparing hard carbon material from a carbon precursor according to claim 1, characterized in that: The two-stage high-temperature carbonization sintering described in step S2 is sintered by heating to the sintering temperature in two stages at a heating rate of 6-15°C / min and 1-5°C / min. The two-stage sintering temperatures are 800-1100°C and 1200-2000°C, and the two-stage sintering time is 0.5-4h and 1-6h. The protective atmosphere is at least one of vacuum, argon, nitrogen, and ammonia.

5. The method for preparing hard carbon material from a carbon precursor according to claim 1, characterized in that: The pulverization in step S2 is mechanical pulverization, including coarse pulverization and fine pulverization; the pulverization also includes screening and grading.

6. The hard carbon material prepared by the method according to claims 1-5, characterized in that: The specific surface area of ​​the hard carbon material is ≤27m 2 / g, tap density ≥0.50g / cm 3 , average particle size D50≤20μm.

7. Use of the hard carbon material according to claim 6 as a negative electrode material for an alkali metal ion battery.

8. The hard carbon material according to claim 7, characterized in that The alkali metal ion battery consists of a positive electrode, a separator, an electrolyte and a hard carbon negative electrode.

Citation Information

Patent Citations

  • A preparation method of biomass hard carbon material for negative electrode of sodium ion battery

    CN109004199A

  • Durian shell-based hard carbon negative electrode material and preparation method thereof

    CN115650202A